Rêves de fleurs et rêves de fruits : une construction andine du genre - Palmira La Riva González (Journal de la Société des Américanistes)
Dreams of flowers and fruits. The Andean construction of gender. A rich literature about gender has demonstrated that the roles and behaviours assigned to men and women are social constructions varying within and across cultures and changing over time. These representations of gender are tightly related to the conceptions of the body and personhood. Our intention is to demonstrate how, in the Southern Peruvian Andes, the man/woman opposition, although having a biological explanation, have to be reinforced during the beginning of the life cycle of every person, by discourse and ritual practices modifying the body.